Soccer strategies : attacking, defending, goaltending - Fairclough, Paul, coach (Buffalo, N.Y. ; Richmond Hill, Ont. : Firefly Books, 2009)
Novice and skilled players can learn to improve their soccer skills and tactics, whatever their team position.
Profile of an attacker -- Shooting for goal -- Heading for goal -- R eceiving the ball -- Passing for attackers -- Losing your marker -- Run ning with the ball -- Crossing the ball -- Tricks for attackers -- Shie lding the ball -- Attacker's challenge.
Keywords: Soccer -- Training